دراست يقارنت نفاعهيت ادارة انىقج وعلاقخها بانخحصيم انذراسي بين طلاب و طانباث ان زًحهت الاون وانزابعت نكهيت انخزبيت انزياضيت في انجايعت ان سًخنصزيه - سندس موسى جواد (الرياضة المعاصرة)
Provided and the importance of research The time is one of the scarce resources in the community is required to exploit better than before, but the educational process, namely, (teacher and student) is not the goal of the educational process to teach the scientific material only, but work on getting the best scientific achievements. But the multiplicity of tasks due both teacher and student alike across the hours of the school day, the time problem arise in all activities so they do not expand the time available to complete all the work required. The process of education does not depend on the teacher just use his mind as a store of information or on memorization only, but the amount and the changing role of both teacher and learner Valmtalm became involved in all what is happening has been providing educational positions for the teacher to make it capable of positive interaction with the learner, which helps or reflect access to learn the best and therefore achieve the desired goals of the process